PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, PROFITABILITAS TERHADAP KEBIJAKAN HUTANG (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia periode 2012-2016) - Dewi Nur Khusniyah; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe study aims to empirically test the impact of Managerial Ownership,Institutional Holdings, Dividend Policy, and Profitability on Debt Policy ofmanufacturers listed in Indonesia stock Exchange from 2012 to 2016. The dataare taken from a five-year period, which is from 2012 to 2016.The study uses quantitative method. The samples are obtained by usingpurposive sampling. There are ten manufacturers which are qualified to be thesamples. The study uses multiple linear regression technique.The result of the study shows that, Managerial Ownership does notsignificantly affect Debt Policy indicated by coefficient which is 1.432 withprobability which is 0.159. Institutional Holdings does not significantly impact ondebt policy implied by coefficient which is 1.033 with probability which is 0.307.Dividend Policy does not considerably influence on Debt Policy confirmed bycoefficient which is 1.202 with probability which is 0.236. Profitability does notsignificantly impact on Debt Policy proven by coefficient which is 1.533 withprobability which is 0.132. Simultaneously, Managerial Ownership (MOWN),Institutional Ownership (INSWN), Dividend Policy (DPR), and Profitabilityimpact (ROA) on Debt Policy (DER) which is confirmed by F value which is2.280 with probability which is 0.075. The multiple linear regression formula ofthe study is:Y = 56.017 + 1.674X1(Sig. 0,159) + 41.226 X2(Sig. 0,307) + 9.734 X3 (Sig.0,236) -112.344 X4 (Sig. 0,132) + e.Keywords: Managerial Ownership, Institutional Ownership, Dividend Policy,and Profitability on Debt Policy